If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+2/3X+72=216
We move all terms to the left:
X+2/3X+72-(216)=0
Domain of the equation: 3X!=0We add all the numbers together, and all the variables
X!=0/3
X!=0
X∈R
X+2/3X-144=0
We multiply all the terms by the denominator
X*3X-144*3X+2=0
Wy multiply elements
3X^2-432X+2=0
a = 3; b = -432; c = +2;
Δ = b2-4ac
Δ = -4322-4·3·2
Δ = 186600
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{186600}=\sqrt{100*1866}=\sqrt{100}*\sqrt{1866}=10\sqrt{1866}$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-432)-10\sqrt{1866}}{2*3}=\frac{432-10\sqrt{1866}}{6} $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-432)+10\sqrt{1866}}{2*3}=\frac{432+10\sqrt{1866}}{6} $
| (x-1)(x-1)=(2x+1)(x+1)-(x+3)(x+3) | | 0.5p+-3.45=-1.2 | | 11/2+t=31/2;t=2 | | 12x-9=4x-15 | | h=169 | | 10=2(4x+3) | | 2/5(1/2y+5)−4/5=1/2y−1+-11/0y | | 36c=1,116 | | (x-1)²=(2x+1)(x+1)-(x+3)² | | 0.8x=12. | | 3/x-1=4/x-1 | | 12+f=29 | | (x-1)^2=(2x+1)*(x+1)-(x+3)^2 | | Y=0.99x+0.96 | | 9/12=x/12 | | 5x+2+3x+6=360 | | 1.8g=-27 | | 5x+2+3x+6=180 | | -24x+4^x=-32 | | (x-1)(x-1)=(2x+1)*(x+1)-(x+3)*(x+3) | | f(-2)(0)=-5^2-20 | | 1^5x+2=243 | | -7/2+2/7u=-8/3 | | (2x–3)=(13x–41)=180 | | (-2)(x)=-5^2-20 | | 3^(2x)=17 | | -6.7=b-2.5 | | 1-6x=3/2x+7 | | −18+5z=37 | | 3.1*x=55.8 | | m-7=-19 | | 0.12x=3.36 |